2017
DOI: 10.1021/acs.jpcc.6b12204
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Ionic Dynamics Coupled at Solid–Liquid Electrolyte Interfaces in Porous Nanocomposites of Carbon Black, Poly(vinylidene fluoride), and γ-Alumina

Abstract: Better fundamental understanding of the transport properties within nanocomposite materials consisting of interpenetrated percolating networks and used as electrodes is needed to improve their performance for a variety of devices. The simultaneous measurement of their effective ionic and electronic conductivities requires a sophisticated experimental set up. Here, the reciprocal influence of ionic and electronic transfers at different scales of model porous nanocomposites made of carbon black–poly­(vinylidene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 55 publications
2
26
0
1
Order By: Relevance
“…Panabière et al . 56 showed that electrons transport mechanism in carbon/polymer mixtures used in battery field was tunneling with no temperature dependence (metal-like behavior). Nonetheless, such temperature dependence would be perceived when strong dipoles are adsorbed at the carbon particles surface.…”
Section: Resultsmentioning
confidence: 99%
“…Panabière et al . 56 showed that electrons transport mechanism in carbon/polymer mixtures used in battery field was tunneling with no temperature dependence (metal-like behavior). Nonetheless, such temperature dependence would be perceived when strong dipoles are adsorbed at the carbon particles surface.…”
Section: Resultsmentioning
confidence: 99%
“…Given the good electronic conductivity of the active material itself and the density of the composites, the electronic wiring is less likely to be the limiting factor. On the other hand, in contact with the electrolyte, that is, during operation, the electronic conductivity may drop considerably …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in contactw itht he electrolyte,t hat is,d uring operation, the electronic conductivity may drop considerably. [52] In Figure 3c,t he mean potential is plotted against cycling rate.T his is an indicator of the overpotential of the cell reaction as af unctiono fc urrent density.E ach data point represents the average of two measurements.A se xpected, the mean potential during charging (left column) is approximately the samef or all formulations.T he more the discharge rate deviates from the charging rate,t he larger the mean dischargep otential. All laboratory-scale formulations display similar mean discharge potentials up to ar ate of 1C.T he PVdF electroded isplays the lowest overpotential at ar ate of 2C,w hichc ould be related to the formationo fapolymerelectrolyteg el at the electrode-electrolyte interface, owing to extensive material swelling.…”
Section: Rate-capabilitye Xperiments In Graphite-lithiumhalf-cellsmentioning
confidence: 99%
“…It can be observed that the pure resistance at high frequencies decreases when the temperature increases (Figure b). The first depressed semicircle that was attributed to the contact between the electrode layer and the current collector is not influenced significantly by the temperature, which is typical of electron transport or transfer . The second feature, which was attributed to the distribution of the charge transfer phenomenon through the electrode thickness, is significantly influenced by the temperature.…”
Section: Resultsmentioning
confidence: 97%
“…The first depressed semicircle that was attributed to the contact between the electrode layer and the current collector is not influenced significantly by the temperature, which is typical of electron transport or transfer. [38] The second feature, which was attributed to the distribution of the charge transfer phenomenon through the electrode thickness, is significantly influenced by the temperature. The amplitude decreases when the temperature increased, as reported in the literature for the charge transfer resistance.…”
Section: Eis Analysismentioning
confidence: 99%